Pengaruh Beban Kerja Coder dan Ketepatan Terminologi Medis Terhadap Keakuratan Kode Diagnosis Penyakit Gigi di RSJ Grhasia DIY Tahun 2012 - Riyanti, Ning, Ibnu Mardiyoko, SKM., MM, Arief Kurniawan Nur Prasetyo, SKM (2013)
Implementation officer with the border coding coding for data gathering from reporting, the results have not been confirmed coding with service providers. Luxasi coding group entry with the letter K is K05.5, there are problems that make coding a lack of understanding between the officers with service providers, medical terminology errors in the selection of approximately 10% which resulted in inaccurate diagnosis codes. K05.5 other periodontal diseases, dislocation of tooth S03.2. Research objectives: determine the effect of workload for the accuracy coder medical terminology RSJ Grhasia DIY in 2012. Research design used a time series approach. Object of study: DRM dental patients. Subject: coding clerk. Samples: the total sample of 1543 DRM. Analytic analysis: normality test datadengan Kolmogorov Smirnov test with the help of the computer program SPSS (Statistical Package for Social Science) for windows and multiple linear regression, the formula: Y = a + + b1X1 b2X2. RESULTS: The average time to encode the DRM = 14 minutes. Workload standard coder DRM 30 per day. There are significant workload variables ketapatan coder and medical terminology to code the accuracy of diagnosis of dental disease in the value of p = 0.006 (<0,05). Code Inaccurate 21.1%